Fast Italian - Smith, Elisabeth (London hodder education, 2011)
Look no further. In just 35 minutes a day for six weeks, Elisabeth Smith will teach you the 450 most useful words and expressions that you need. Whether you're going on holiday, looking to brush up lost language skills or just curious about Italian, this course will give you the confidence to communicate in all kinds of everyday situations - shopping, chatting over a coffee, ordering a meal, setting up a meeting, booking a hotel. You'll be able to speak to the locals - and understand what they say back to you!
Keywords: Conversation; Italian language